The challenges of managing ethnic diversity in the workplace: the case of non-governmental organisations in South Sudan - Masua, David (2020)
South Sudan is a new country having gotten independence in 2011 from the Sudan. A Country of 64 ethnic groups, South Sudan is deeply divided along ethnic lines and this has permeated throughout social, economic and political fabric of the country. Consequently this minor field study was conducted to investigate the challenges NGOs face managing ethnic diversity. Specifically the study investigated the influence of ethnic diversity on staff recruitment and selection, how NGOs manage ethnically diverse staff, the challenges they face and how they manage these challenges.